Pengaruh Beberapa Tingkatan Suhu Ruang Terhadap Waktu Perkembangan Cryptolestes ferrugineus Stephens - Pratiwi, Ni Putu Eka; Ananda, Komang Dean (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2020)
Cryptolestes ferrugineus (Cucujidae: Laemophloeidae) is a postharvest secondary pest of rice and other food commodity products. The distribution of C. ferrugineus covers tropical or subtropical climates with high humidity. Temperature fluctuations that occur every day affect development C. ferrugineus. The development of the life phase of C. ferrugineus largely determines the amount of its population and its massive impact on the damage caused to storing material. This research was conducted to determine the effect of several levels of room temperature on the development time of C. ferrugineus. The room temperature used in this study was 20°C, 25°C, 30°C, 35°C, and 40°C and was repeated five times. The results showed that the shortest development time of the insect pest C. ferrugineus (26.75 days) occurred at a room temperature of 30°C with a humidity of 68% compared to other room temperatures. The slowest development time for C. ferrugineus occurs at 25°C (42.60 days). At room temperature 40°C eggs produced by adult female C. ferrugineus cannot develop into larvae, so the development C. ferrugineus at 40°C was cut off.